Democratic Responsiveness in the European Union: the Case of the Council - Christopher Wratil (London School of Economics and Political Science (LSE), European Institute, 2015)
Governments' responsiveness to citizens' preferences is a key assessment criterion of democratic quality. This paper assesses responsiveness to public opinion in European Union politics with the example of governments' position-taking in the Council of the EU. The analysis demonstrates that governments' willingness to adopt negotiation positions that reflect public opinion systematically varies with their electoral incentives flowing from domestic arenas. Governments behave responsive in EU legislative negotiations if they face majoritarian electoral systems at home, when elections are imminent, and when parties or EU-related events trigger the public salience of integration. These findings have important implications for the debate on the EU's democratic deficit and our understanding of democratic responsiveness outside the national political arena.
Keywords: 330; responsiveness; public opinion; European Union; multidimensional; democratic deficit